Costing for strategy development and analysis in an emerging industry: The Newcastle Upon Tyne Electric Supply Company, 1889–1914. Issue 3 (May 2017) - McLean, Tom; McGovern, Tom
Abstract: This article examines the provision of strategic costing information in the context of the emergence and growth of the British electrical power industry and its pre-eminent exemplar, the Newcastle Upon Tyne Electric Supply Company (NESCo). A detailed case study of NESCo's costing for strategy development and analysis is presented. This research finds that NESCo's adoption of systematic, formal considerations of strategy and its use of costing for strategy development and analysis were related to a combination of three factors: first, the novelty and complexity of the electricity supply industry; second, the regulated environment of the electricity supply industry; and third, the ability and drive of key individuals. The implications of this research for contemporary studies of strategic management accounting are considered.